System of drugs circulation based on medical and pharmaceutical law - Shapovalova, Viktoriya (Actual Problems of Medicine and Pharmacy, 2021)
It is proved that the harmonization of medicine and pharmacy to the EU requirements is based on the components of medical and pharmaceutical law: medical legislation, pharmaceutical legislation, forensic pharmacy, evidence-based medicine, evidence-based pharmacy, drug control regime. An interpretation of the components of medical and pharmaceutical law is given. The system of circulation of medicines is resulted.